1 Fed. Reg. 668, 674, National Park Service Rules and Regulations (1936) - (:unkn) unknown (My University, 1936)
§ 8: Prohibited firearms, explosives, traps, seines, and nets within the parks and monuments under federal control.
Keywords: CARRY - CERTAIN PUBLIC PLACES